"They're not leaving their home; this is where they were born, this is where they will die.": Key Informant Perspectives From the U.S. Counties With the Greatest Concentration of the Oldest Old. (March 2022) - Henning-Smith, Carrie; Lahr, Megan; Tanem, Jill
The "oldest old, " age 85 and older, constitute one of the fastest growing segments of the U.S. population. Yet, surprisingly little is known about the characteristics of U.S. counties with the highest percentage of the oldest old, nearly all of which are rural. We used qualitative analysis of key informant interviews ( n = 50) with county commissioners and other county-level representatives from rural counties with the highest prevalence of the oldest old, targeting the 54 rural counties with ≥5% of the population age 85+. We found that the rural counties with the highest proportion of residents age 85+ face unique challenges to supporting successful aging among the oldest old, including resource constraints, limited services, isolated locations, and widespread service areas. Still, interviewees identified particular reasons why the oldest old remain in their counties, with many highlighting positive aspects of rural environments and community.